Avaliação do Método Monte Carlo para predição da densidade de líquidos iônicos e de sua aplicação para absorção de CO2 - Silva, Paulo Henrique Ramos (2018)
The ionic liquids synthesis' possibilities, by combining different cations and anions, are almost boundless. This has aroused academic and industrial community's interest, aiming its application in several areas such as catalysis, biocatalysis, extraction and separation; and electrochemistry. Many recent research reinforces this kind of solvents’ importance on CO2 and H2S capture processes. Therefore, it is desirable to develop tools capable to predict the properties of a potencial Ionic Liquid before its synthesis. In this context, the molecular simulation has proven to be a powerful tool. The molecular simulation basis, using the dynamic and Monte Carlo methods, is a description of the potential interactions between the atoms through force fields. In order to clarify the relevance of intrinsic variables of Monte Carlo method and the force field parameters in the prediction of ionic liquids density and carbon dioxide solubility in these liquids, a parametric study, involving protic and aprotic ionic liquids, was developed by using Cassandra software. Different accounting methods for electrostatic interactions, force fields and motion probability were evaluated. The results showed that the Damped Shifted Force method has reduced the processing time with no results quality loss. The use of dihedrals probability proved to be important to some aprotic ionic liquids when using CHARMM force field, especially in imidazolium compounds based ionic liquids. Force fields have not been systematically studied for protic ionic liquids properties prediction and tried force fields, developed by using different tools, have denoted that they are not easily transferable.